Cравните выражения:

1). a^2+b^2>2(a+b-1)

2). (a^3-b^3)(a-b)>3ab(a-b)^2

3). a^2+3>2a

4). b^2+25>10|b|

5). a^4+b^4+ab(a^2+b^2)>0

6). (a+b)^3<4(a^3+b^3)

7). a^3-b^3>3ab(a-b)

1

Ответы и объяснения

2012-10-16T23:06:44+04:00

1. (a-1)^2+(b-1)^2>=0

2.(a-b)^2(a^2+ab+b^2)>=3ab(a-b)^2, (a-b)^2>=0

3. (a-1)^2+2>0

4.(b+-5)^2>=0

5.(a^2-b^2)(a^2+b^2)+ab(a^2+b^2)>0 , a^2-b^2+ab>0 , a^2+ab-ab-b^2+ab>0, a^2+ab-b^2>0

6.a^3+3a^2*b+3b^2*a+b^3>4*(a^3)+4*(b^3), a^3+b^3-a^2*b-b^2*a<0

7.(a-b)(a^2+ab+b^2)>3ab(a-b) , (a-b)^2>=0